(untitled) (American Journal of Islam and Society, 1990)
Muhammad Anwar’s "Modelling Interest-Free Economy: A Study In Macroeconomics and Development" (1987) and subsequent comment by Tekir (1989) deserve serious consideration. Anwar’s general macroeconomic model is one of the few models which offer a synthesis of traditional Classical and Keynesian models of macroeconomy. However, there are some fundamental theoretical and empirical weaknesses, some of which will be discussed briefly. Although the proposed "Interest-Free" monetary system is based on the principle of competitive markets (Tekir, 1989), it has no explanation for the extent of government’s involvement in the macroeconomic activity. Even if we temporarily set aside the implicit assumption of a morally just monetary system, the proposed system of "Mudarabas" has serious limitations. For instance, the government purchases of goods and services will have to be either financed by increased taxes, monetization or by selling "Mudarabas" in the National or international market. (1) The "Mudaraba" contracts will replace the traditional bond-financed method of borrowing by government. If we rule out the highly inflationary monetization method, the only plausible method is the sale of "Mudarabas." It will tend to have the same degree of crowding out as expected in the bonds-financed method. As pointed out by Tekir (1989), the system opens itself to an undue intervention by government and lacks efficient allocation of resources. It is likely that a politically determined allocation of resources by government will be less than efficient. Moreover, the traditional productivity-based method of evlauating the benefits cannot be used. The output produced in the public sector may be evaluated on non-market criteria, an aspect completely ignored by Anwar’s model. On a more general level the concept of "Mudarabas" will eliminate the bonds market and replace that with an equity market. This will be an equivalent of the stock market, which shows the strong, speculative element worldwide, an activity discouraged by Islamic economics. The stock market volatility in the U.S. and worldwide in 1987 and 1989, shows that the "Mudaraba" market will have to be modified to reduce the element of speculation. In more recent years, real estate markets in many Muslim countries have shown tremendous overvaluation due to highly speculative activities. An inflationary pressure in Mudaraba-based economy may also be another cause of volatility. Lastly, Anwar’s claim that interest rates are negatively associated with budget deficits lacks empirical evidence. There is some evidence (Volker ...